2008
DOI: 10.1371/journal.pbio.0060298
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of Neuroeconomics: From Philosophy to Practice

Abstract: How can we use neuroscience to better understand economic behavior? By quelling concerns about the nascent field of neuroeconomics, the authors defend future integrations of the biological and social sciences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 96 publications
(125 reference statements)
3
38
1
Order By: Relevance
“…At this time, the mean intensity of keypress behavior (K) has been associated with reward circuitry activity [14], [18], cortical thickness measures [19], and foci of genetic variability [18], [20], while variance-mean plots in electrophysiology [38] approximate the saturation plots we see with keypress behavior. These findings with (K) and (σ) variables underline the biological plausibility of the patterns described herein [124]. The apparent scaling of all patterns between group and individual data support the neuroeconomic perspective [10], [11], [33][37], [124] of combining engineering [64], [127], systems modeling [60], and neuroscience [128][130] approaches to the study of choice behavior, and may provide a route for quantitative phenotyping of psychiatric illness [47]–[49].…”
Section: Discussionsupporting
confidence: 77%
“…At this time, the mean intensity of keypress behavior (K) has been associated with reward circuitry activity [14], [18], cortical thickness measures [19], and foci of genetic variability [18], [20], while variance-mean plots in electrophysiology [38] approximate the saturation plots we see with keypress behavior. These findings with (K) and (σ) variables underline the biological plausibility of the patterns described herein [124]. The apparent scaling of all patterns between group and individual data support the neuroeconomic perspective [10], [11], [33][37], [124] of combining engineering [64], [127], systems modeling [60], and neuroscience [128][130] approaches to the study of choice behavior, and may provide a route for quantitative phenotyping of psychiatric illness [47]–[49].…”
Section: Discussionsupporting
confidence: 77%
“…Yet, the plausibility of the "common currency hypothesis" of reward does not seem to be affected (Kringelbach andBerridge, 2010, Leknes andTracey, 2008, 318). In accordance with the methodological considerations presented above, we thus conclude that the assumption of multidimensional utility lacks "biological plausibility" (Clithero et al 2008). …”
Section: Neuroeconomic Insights On Utilitysupporting
confidence: 86%
“…At root, the empirical data needed to establish whether discounting functions follow a hyperbolic, quasi-hyperbolic, or some other function will come from rigorous behavioral testing. What functional neuroimaging data can provide, however, is the ability to evaluate what classes of models are biologically plausible and, thus, are good candidates for future behavioral testing (see Clithero, Tankersley, & Huettel, 2008, for additional discussion). As an example, Delgado and colleagues have demonstrated that a neurobiologically based model can motivate the design of auctions in a study of overbidding behavior (Delgado, Schotter, Ozbay, & Phelps, 2008).…”
Section: Distinguishing Models and Their Constituent Processesmentioning
confidence: 99%